Dynamic decentralised algorithms for cognitive radio relay networks with multiple primary and secondary users utilising matching theory. Issue 5 (29th May 2013) - Bayat, Siavash; Louie, Raymond H. Y.; Vucetic, Branka; Li, Yonghui
ABSTRACT: We propose a distributed spectrum access algorithm for cognitive radio relay networks with multiple primary users (PUs) and multiple secondary users (SUs). The key idea behind the proposed algorithm is that the PUs negotiate with the SUs on both the amount of monetary compensation, and the amount of time the SUs are either (i) allowed spectrum access, or (ii) cooperatively relaying the PU's data, such that both the PUs' and the SUs' minimum rate requirements are satisfied. The proposed algorithm is shown to be flexible in prioritising either the PUs or the SUs. We prove that the proposed algorithm will result in the best possible stable matching and is weak Pareto optimal. Numerical analysis also reveals that the distributed algorithm can achieve a performance comparable to an optimal centralised solution, but with significantly less overhead and complexity. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : We propose a distributed spectrum access algorithm for cognitive radio relay networks. Our algorithm determines the matched pairings between PUs and SUs, such that the SU will provide monetary compensation, and relay its paired PU's data in exchange for spectrum access. The matchings are stable and optimal for the PUs.